The many faces of Pulmonary Langerhans Cell Histiocytosis - Biswas, Abhishek; Donahoe, Michael P (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2014)
Langerhans Cell Histiocytosis is a rare disease with variable presentation and prognosis in adults and in children. Histiocytosis of the ocular choroidal tissue has never been reported before in adults. We present two cases, one with choroidal involvement with asymptomatic nodulo-cystic changes in the lungs and another case with advanced single organ pulmonary involvement. We discuss the various treatment modalities and highlight the lack of adequate guidelines to treat adults. Most of the current guidelines are based on evidence derived from pediatric literature. We would also like to draw attention to the asymptomatic nature of the lung involvement and suggest that imaging of the lung be obtained in all cases of Langerhans Cell Histiocytosis.